2016
DOI: 10.3382/ps/pew043
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes of Insulin-like growth factors in the liver and muscle of chick embryos

Abstract: The insulin-like growth factors ( IGFS: ) are synthesized in tissues and play an important role in embryonic development of avian via autocrine/paracrine mechanisms. In the study, mRNA expression of IGFs were detected by real-time PCR in the muscle and liver from d 10 to 20 of chick embryo ( E10: to E20: ). Methylation of IGF1 promoter in the muscle was analyzed by bisulfite sequencing PCR as well as IGF2 promoter in the liver. These results showed that there was obviously IGF1 expression in liver at E19 and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…DNA methylation is catalyzed by DNA methyltransferases (DNMTs). DNMT1 is a maintenance methyltransferase and responsible for restoring the methylated status of newly synthesized daughter strands; DNMT3a and DNMT3b are de novo methyltransferases (Li et al, 2016). Consistently, these DNMTs expression were also not affected by folic acid supplementation in the current study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…DNA methylation is catalyzed by DNA methyltransferases (DNMTs). DNMT1 is a maintenance methyltransferase and responsible for restoring the methylated status of newly synthesized daughter strands; DNMT3a and DNMT3b are de novo methyltransferases (Li et al, 2016). Consistently, these DNMTs expression were also not affected by folic acid supplementation in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Primers sequences were shown in table 1. Detailed procedures were operated as our previous description (Liu, et al, 2016). The 2 −ΔΔ Ct method was used for gene relative expression (Livak and Schmittgen, 2001).…”
Section: Rna Isolation and Gene Quantificationmentioning
confidence: 99%
“…In addition to its key role in whole-body, glucose and lipid homeostasis, this organ is also a major site of the synthesis of plasma proteins and endocrine factors such as insulin-like growth factor 1 and 2 (IGF1 and IGF2), as well as their binding proteins (IGFBPs) and thereby influences whole-body metabolism and growth [ 1 ]. The circulating IGFs do not represent the true level of tissue secretion, though they may reflect organ development to some extent [ 2 ]. Moreover the role of the liver in the secretion of IGF1 and IGFBPs, is not only under endocrine and nutritional control, but also under autocrine and paracrine control [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…During development, both cTNNC and sTNNC are expressed in embryonic skeletal muscle, but expression of the cTNNC gene is subsequently turned off during the transition to fast-twitch muscle[ 27 ]. IGFs are synthesized in tissues and play an important role in embryonic development in birds via autocrine/paracrine mechanisms[ 28 ]. Higher IGF1 expression levels were found in muscle from E15-E18 with a peak at E17 followed by a decline during chick embryonic development[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGFs are synthesized in tissues and play an important role in embryonic development in birds via autocrine/paracrine mechanisms[ 28 ]. Higher IGF1 expression levels were found in muscle from E15-E18 with a peak at E17 followed by a decline during chick embryonic development[ 28 ]. We previously reported that IGF1 and MSTN mRNA levels may influence muscle-growth rates in ducks[ 3 ].…”
Section: Discussionmentioning
confidence: 99%